(untitled) (Praxis Educativa, 2020)
Gender and women’s studies have become more visible in recent years. A tangible advance not only in academic terms, but also at a social and educational level. Although these issues have gained notoriety in our country, we note that this does not affect the same intensity in the educational field. At secondary level, these issues enter preferably from the hand of the Comprehensive Sexual Education Law (Law No. 26,150) although this does not happen systematically. We ask ourselves then about the History that is taught not only in high school, but also at University. Within this framework, we promptly inquire into the entry of these issues within the History Teachers Program at the National University of La Plata. In sum, this is a paper that tries to question which historical subjects regain voice in the teaching of university History and at the same time it presents the curriculum as a cultural, historical and gendered device.